2019
DOI: 10.1007/s13178-019-00388-y
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing as Evidence-Based Practice? An Example from Sexual Risk Reduction Interventions Targeting Adolescents and Young Adults

Abstract: This paper critically examines sexual risk reduction interventions, more specifically how they are evaluated and the implications that this has for sexual health policy. The focus is on motivational interviewing (MI) interventions which aim to promote protective behaviors related to sexual risk on the part of young people. MI has become increasingly popular, largely due to it being a highly flexible counseling approach that may, with adequate staff training, and fidelity in implementation, be tailored to many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Tying HIV education to the broader goals and values of men is critical to helping men identify how HIV treatment can specifically benefit their lives, and therefore, increases individual buy-in and commitment to treatment [55,[73][74][75][76][77]. We found that motivating explanations were usually provided "sometimes" not "often."…”
Section: Discussionmentioning
confidence: 91%
“…Tying HIV education to the broader goals and values of men is critical to helping men identify how HIV treatment can specifically benefit their lives, and therefore, increases individual buy-in and commitment to treatment [55,[73][74][75][76][77]. We found that motivating explanations were usually provided "sometimes" not "often."…”
Section: Discussionmentioning
confidence: 91%
“…When considering sexual health speci cally, it is likely that re ecting on the personal relevance of one's sexual wellbeing will increase motivation to change. Using motivational interviewing techniques is one evidence-based way of achieving this shift [23,24]. The model suggests that an intervention in this area should therefore focus on the following: Information (education) about the issues to improve knowledge of sexual wellbeing (e.g., HIV, STIs, contraception, risk behaviours, and what respectful, safe relationships should look like); Motivation, such as weighing up the pros and cons of contraception, mediating risk perception, and issues around consent;…”
Section: Identifying Theorymentioning
confidence: 99%
“…Here, too, it is possible to apply the whole RSH interview (when preferred, in an adjusted form), or certain parts of it for treatments in sexology or relationship therapy. The RSH interview method can also be combined with principles of Motivational Interviewing (MI), by integrating it with the process of formulating an improvement plan toward healthy and pleasurable intimate relationships and sexuality of young adults (Bahner and Stenqvist, 2020). Furthermore, using the RSH interview method can increase cross-pollination between these clinical fields, by paying more attention to relational context of sexological problems, and by paying more attention to the role of sexuality in (causing or solving) relationship problems.…”
Section: Clinical Applicabilitymentioning
confidence: 99%